If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -10 = -20 Reorder the terms: -10 + 6x = -20 Solving -10 + 6x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 6x = -20 + 10 Combine like terms: -10 + 10 = 0 0 + 6x = -20 + 10 6x = -20 + 10 Combine like terms: -20 + 10 = -10 6x = -10 Divide each side by '6'. x = -1.666666667 Simplifying x = -1.666666667
| 14fa-72a^2+f^2= | | 2/3g=6=-12 | | -5z+6=6z-38 | | 144=-12(X+-60) | | a*bcd=bcd*a | | 1X+8=3X+14 | | (x+y)=3(x+y)-2 | | 4x-(3x-7)-(2x-3)=8x(x-1) | | 8z+4=11z-17 | | 3x+4(1)=-2 | | 5(2u-2)-12u= | | 5m+2n-2m+9n= | | 2x+12=3x-8 | | 9+3r=-17 | | -72+11y+2=4(5y-2)-8 | | -2(2-5x)=8x-2 | | 14qp-51q^2+p^2= | | -5x-3x+9x=4-x | | 1/2x=1/4-6 | | w/7=3=-1 | | 2(2-5x)=8x-2 | | 13=-10y+3y | | 4(x-3)(x+4)=0 | | 5y-y=-12+y | | 2.5=(x-54166)/10200 | | 4(5x-3)+9=-2 | | (6x+2)(7x^2-5x-4)= | | 2x-10=38 | | -9r+1=-80 | | 3x8/3 | | mx^2+(2m-1)x+(m-1)=0 | | 5=x/4=1 |